Constructing Political Image in Campaign Billboards: A Critical Discourse Analysis of Kaesang Pangarep - Andi Mega Januarti Putri; Nurul Imansari; Putu Wahyu Sudewi (GLENS: Global English Insights Journal, 2026)
Political campaign billboards play an important role in shaping public perception and constructing political identities through the integration of linguistic and visual elements. This study examines how Kaesang Pangarep’s campaign billboards construct political meaning and image using a multimodal critical discourse approach through Critical Discourse Analysis. The data includes six campaign billboards, each containing a unique slogan and visual elements. The results suggest that informal and colloquial language, cultural references, metaphors, and playful use of lexis frame politics as accessible, youthful, and relatable. These messages are visually reinforced through smiling expressions, relaxed gestures, collective imagery, and deliberate composition. The steady presence of Jokowi’s name and image serves to reinforce the legitimacy of the candidate by associating him with a known leader. The synergy between words and pictures constructs a political image, portrayed as youthful, creative, approachable, progressive, and credible. How campaign billboards supplement the construction of political identity through persuasive discursive tools enriches the field of multimodal political communication research. Nonetheless, the analysis is limited to discursive representation and does not establish how audiences receive these productions. Future research may look at which levels resonate with voters, and whether or not multimodal campaign tactics are effective in shaping perceptions.